Comparison of the content in Palestinian Mathematical Textbooks for grades 3-5 with the Palestinian Document of Mathematics in light of the content standards of numbers and operations set by the National Council of Teachers of Mathematics (NCTM) - Karzoun, Noor Anees (Dirasat: Educational Sciences, 2023)
Objectives: The current study aims to identify the standards in the Palestinian mathematical textbooks for the third grade to the fifth grade and the Palestinian document of mathematics, to determine their compatibility in the light of the (NCTM) content standards of numbers and operations. Methods: To achieve the objectives of the study, the researcher used the analytical descriptive approach. The study sample consisted of 19 study units in the content of numbers and operations in textbooks and in the mathematics document issued by the Curriculum Center (2016). The researcher used a content analysis card derived from (NCTM, 2000) standards that students should fulfill in grades (3-5). Results: The study results showed that most of the sub-standards were found in both textbooks and the document. In addition, The compatibility level of the content of the Palestinian Mathematics textbooks for grades (3-5) with the Mathematics Document based on (NCTM) content standards of numbers and operations ranged from (high to excellent) in the light of the study scale. Conclusions: The study recommends enriching the new edition of mathematics books for grades (3-5) with paragraphs that considerate (NCTM) standards in the fields of numbers and operations as they were either not included in the document or the mathematics textbooks, or both. Furthermore, these books should contain paragraphs that help students understand mathematical ideas and operations conceptually by using estimation, mental arithmetic, visual models and diagrams, and activating the use of calculators in performing calculations on natural numbers, fractions and solving problems.